(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
This paper investigated the wear performances of Y2O3 doped MA6000 (Ni-Cr-Al) alloy produced by mechanical alloying (MA). Produced, all powders were pre-formed by cold pressing and sintered in a vacuum environment. Sintered MA6000-X% Y2O3 superalloys were characterized by scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), X-ray diffraction (XRD) analysis, density, and hardness measurements. Wear tests of Y2O3 added MA6000 alloys were carried out in a block-on-ring type wear device. In the wear tests, the sliding speed of 1 ms-1 at room temperature (RT) was performed under five different sliding distances (200-1000m) and three different loads (5 N, 10 N, and 15 N). As a result of the studies, it was determined that the MA’ed MA6000 superalloy powders were homogeneous and flake shape. With the increase amount of Y2O3, hardness of these superalloys increased from 267 to 431 Hv, but the density slightly decreased. Different intermetallic/carbur phases such as Ni3Al, MoC are observed in all compositions. Wear tests show that weight loss and wear rate decreased, and friction coefficient (µ) increased with the increasing amount of Y2O3 additive. Besides, it was determined that as the applied load increased in the wear test, the weight loss increased, but the wear rate and friction coefficient (µ) decreased.